Pengembangan LKPD Berbasis Pendekatan Saintifik pada Tema Sumber Daya Alam di Kelas IV Sekolah Dasar : Penelitian - Siti Nurjannah Munthe; Beta Rapita Silalahi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the feasibility of LKPD Media on the theme of natural resources in Grade IV Elementary School. This study is a development research (Research and Development) using the ADDIE development model which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. However, this study only goes up to three stages, namely only up to the Development stage. The instrument used to collect data is a questionnaire. The data analysis technique used is a qualitative descriptive analysis technique. From the validation results with a language expert validator, a score of 80 was obtained with the criteria of "Feasible" for the language systematics in the LKPD being developed. From the validation with a material expert validator, a score of 90.8 was obtained with the criteria of "Very Feasible" for the material in the LKPD being developed. From the learning expert validator, a score of 96.8 was obtained with the criteria of "Very Feasible". From these results, it can be said that the LKPD based on the scientific approach to the theme of natural resources that was developed is "Very Suitable" for use in the learning process in class IV of SD Nurul Islam Indonesia.